Metabolic Surgery to Treat Obesity in Diabetic Kidney Disease, Chronic Kidney Disease, and End-Stage Kidney Disease; What Are the Unanswered Questions? - Martin, William P.; White, James; López-Hernández, Francisco J.; Docherty, Neil G.; le Roux, Carel W. (Frontiers in Endocrinology, 2020)
Obesity is a major factor in contemporary clinical practice in nephrology. Obesity accelerates the progression of both diabetic and non-diabetic chronic kidney disease and in renal transplantation both recipient and donor obesity increases the risk of allograft complications. Obesity is thus a major driver of renal disease progression and a barrier to deceased and living donor kidney transplantation. Large observational studies have highlighted that metabolic surgery reduces the incidence of albuminuria, slows chronic kidney disease progression, and reduces the incidence of end-stage kidney disease over extended follow-up in people with and without type 2 diabetes. The surgical treatment of obesity and its metabolic sequelae has therefore the potential to improve management of diabetic and non-diabetic chronic kidney disease and aid in the slowing of renal decline towards end-stage kidney disease. In the context of patients with end-stage kidney disease, although complications of metabolic surgery are higher, absolute event rates are low and it remains a safe intervention in this population. Pre-transplant metabolic surgery increases access to kidney transplantation in people with obesity and end-stage kidney disease. Metabolic surgery also improves management of metabolic complications post-kidney transplantation, including new-onset diabetes. Procedure selection may be critical to mitigate the risks of oxalate nephropathy and disruption to immunosuppressant pharmacokinetics. Metabolic surgery may also have a role in the treatment of donor obesity, which could increase the living kidney donor pool with potential downstream impact on kidney paired exchange programmes. The present paper provides a comprehensive coverage of the literature concerning renal outcomes in clinical studies of metabolic surgery and integrates findings from relevant mechanistic pre-clinical studies. In so doing the key unanswered questions for the field are brought to the fore for discussion.